El impacto ambiental del desarrollo del turismo en las islas del archipiélago Jardines del Rey, Cuba - Acevedo Rodríguez, P.; Pérez Reyes, J. (Geographicalia, 2016)
The quick process of tourist development undertaken in the Archipiélago Jardines del Rey, in the Republic of Cuba, represents a potential factor of environmental interference for the smalls islands that integrate this insular system; these geosystemes are characterized by their notables natural values, high degree of natural conservation, important geoecologys functions and particular natural fragility what makes them spcecially vulnerable before the human impacts. Presenly work, the islands of this archipielago are characterized and is carried out the analysis of the impact waited by the tourist development in the same ones, like a contribution to the clarification of the problem environmental perspective and to alert about the necessity of working in the prevention and evaluation of these aspects, it stops by means of the environmental planning to guarantee the protection of the islands.